A preparation method of isotropic samarium iron nitrogen magnetic powder and isotropic samarium iron nitrogen magnetic powder

The preparation of isotropic samarium nitrogen magnetic powder by HDDR method solves the problems of low production efficiency and easy agglomeration of magnetic powder in the prior art, realizes magnetic powder with high magnetic properties and uniform texture, and improves the efficiency of industrial production.

CN118969491BActive Publication Date: 2025-02-07GANZHOU SAMARIUM PERMANENT MAGNET TECH CO LTD

Patent Information

Application Number
CN202411463490.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing samarium-iron nitrogen magnetic powder has low production efficiency in industrial production, and the texture of the magnetic powder is prone to agglomeration, which affects the uniformity of subsequent magnetic block production.

Method used

Isotropic samarium-ferro-nitrogen magnetic powder was prepared by HDDR method, and the sm-fast coagulation was carried out through Sm2Fe17 ratio and Sm excess, and then hydrogen crushing and airflow crushing were carried out, followed by HDDR treatment and aging treatment, and finally high-temperature nitrogen was carried out. .

Benefits of technology

The high magnetic energy accumulation, residual magnetism and coercive force of samarium-iron nitrogen magnetic powder are achieved, and the texture is loose and not easy to agglomerate, ensuring the uniformity of subsequent magnetic block production and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118969491B_ABST
    Figure CN118969491B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of magnetic material technology, and in particular to a method for preparing isotropic samarium iron nitrogen magnetic powder and isotropic samarium iron nitrogen magnetic powder. A method for preparing isotropic samarium iron nitrogen magnetic powder comprises the following steps: 2 Fe 17 The invention discloses a method for preparing a samarium iron alloy by mixing metal Sm and Fe with an excess of 5% to 10% of Sm, and then melting and rapidly solidifying the metal Sm-Fe alloy flakes; crushing the Sm-Fe alloy flakes to prepare powdered Sm-Fe alloy; subjecting the powdered Sm-Fe alloy to HDDR treatment to obtain an isotropic alloy block; crushing the isotropic alloy block, and subjecting the powdered Sm-Fe alloy to aging treatment to obtain an isotropic alloy powder; subjecting the isotropic alloy powder after aging treatment to high temperature nitriding treatment to obtain Sm 2 Fe 17 N 3 Isotropic magnetic powder. The prepared isotropic samarium iron nitrogen magnetic powder has both high magnetic energy product and coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a preparation method of isotropic samarium iron nitrogen magnetic powder and the isotropic samarium iron nitrogen magnetic powder. Background Art

[0002] SmFeN magnetic powder is a rare earth permanent magnet material. Compared with NdFeB material, it has higher Curie temperature, better corrosion resistance, thermal stability, and high cost performance. Compared with ferrite, it has higher magnetic properties. The isotropic SmFeN magnetic energy product can be as high as 10MGOe or more. It is widely used in micro motor magnetic strips, magnetic materials used in humid environments, functional magnetic materials, etc.

[0003] Compared with traditional methods, the HDDR method has higher production efficiency for the preparation of permanent magnetic materials, which is of great significance for the industrial production of SmFeN magnetic powder. With the development of high technology in modern human society, the requirements for miniaturization and functional compatibility of electronic devices are getting higher and higher, which puts higher requirements on the performance of SmFeN magnetic powder, and also requires that the prepared magnetic powder has a loose texture and is not easy to agglomerate, which is convenient for the uniformity of subsequent magnetic block production.

[0004] Based on this, the present application aims to prepare isotropic samarium iron nitrogen magnetic powder with excellent magnetic properties, loose texture and not easy to agglomerate through the HDDR method. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing isotropic SmFeN magnetic powder and isotropic SmFeN magnetic powder. The obtained isotropic SmFeN magnetic powder has excellent magnetic properties, high magnetic energy product, remanence and coercive force, and is loose in texture and not easy to agglomerate.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing isotropic samarium iron nitrogen magnetic powder comprises the following steps:

[0008] S1. According to Sm 2 Fe 17 Proportioning, weighing metal Sm and Fe with an excess of 5% to 10% Sm, smelting and rapid solidification to form samarium-iron alloy flakes;

[0009] S2, crushing the samarium-iron alloy flakes to obtain a powdered samarium-iron alloy having a particle size of 5 μm to 15 μm;

[0010] S3, performing HDDR treatment on the powdered samarium-iron alloy of the above particle size to obtain an isotropic alloy block;

[0011] S4, crushing the isotropic alloy block into 5 microns to 15 microns, and performing aging treatment to obtain isotropic alloy powder;

[0012] The aging treatment is to heat the crushed isotropic alloy block to 580℃~620℃ and keep it for 15min~20min, then cool it to 250℃~270℃ and keep it for 1h~2h;

[0013] S5. The isotropic alloy powder after aging treatment is subjected to high temperature nitriding treatment to obtain Sm 2 Fe 17 N 3 Isotropic magnetic powder.

[0014] The preparation method provided in the present application is to crush and age the isotropic alloy block after HDDR treatment, and the crushing can ensure the uniform stability of subsequent aging and nitriding. Before nitriding, the samarium-iron alloy is treated by combining high-temperature aging and low-temperature aging, and the aging temperature and time are optimized. The high-temperature aging treatment is beneficial to the formation of a thin layer of samarium-rich phase around the main phase, and promotes the uniform distribution of the eutectic samarium-rich phase around the magnetic powder. The prepared magnetic powder is subjected to a magnetic property test, and the results show that the prepared isotropic magnetic powder shows excellent magnetic properties, and has high magnetic energy product, remanence, and high coercive force. The obtained magnetic powder has a loose texture and is not easy to agglomerate, which is beneficial to ensure the uniformity of the subsequent pressed magnetic block.

[0015] Furthermore, in the smelting and rapid solidification in S1, the melt temperature adopted is 1450°C to 1500°C, and the rotation speed of the water-cooled copper roller is 1.2m / s to 1.5m / s.

[0016] Furthermore, the crushing in S2 includes hydrogen crushing and air flow milling treatments performed sequentially.

[0017] The hydrogen crushing process is to place the samarium iron nitrogen alloy in a hydrogen environment, allowing hydrogen to enter the alloy along the samarium-rich phase thin layer, causing it to expand and break after heating, thereby turning the thin flakes into coarse powder; the air flow grinding process uses high-speed air flow to further crush the samarium iron nitrogen coarse powder into fine powder. The particle size of the powdered samarium iron alloy obtained after hydrogen crushing combined with air flow grinding reaches 5 microns to 15 microns.

[0018] Furthermore, the hydrogen crushing in S2 is carried out in hydrogen at a temperature of 120°C to 180°C and a pressure of 0.04MPa to 0.06MPa for 0.5h to 10h to cause the samarium-iron alloy flakes to expand and break to obtain the samarium-iron alloy coarse powder.

[0019] HDDR is used to produce isotropic samarium iron nitrogen magnetic powder. The process includes four stages: hydrogen absorption, disproportionation, dehydrogenation, and recombination. The essence of this process is that rare earth metal intermetallic compounds absorb hydrogen and disproportionately decompose, and then in the forced dehydrogenation process, the disproportionate products are recombined into the original compound phase with fine grains, thereby achieving the refinement of the material grains (the average grain size is 300 nanometers) and unifying the crystal structure. Furthermore, the specific process of HDDR in S3 includes the following steps:

[0020] (1) Vacuum: Heating from room temperature to 850°C under vacuum conditions for 2 hours;

[0021] (2) Disproportionation: Disproportionation at 850°C, 0.01MPa to 0.1MPa hydrogen atmosphere for 2h;

[0022] (3) Dehydrogenation: slowly raise the temperature to 900°C for vacuum dehydrogenation treatment;

[0023] (4) Argon filling: at 900°C, 0.01MPa~0.1MPa argon filling for 1h;

[0024] (5) Vacuum deargonization: vacuum deargonization at 900 °C for 1 h;

[0025] (6) Vacuum rapid cooling: After deargonization is completed, rapid cooling is completed under vacuum, and the cooling time is 1 hour.

[0026] Furthermore, the nitriding process in S5 is: the nitriding temperature is 530° C., the nitriding pressure is 0.1 MPa to 1.0 MPa, the nitriding gas used is nitrogen, and the nitriding time is 10 h to 20 h.

[0027] The invention also provides an isotropic samarium iron nitrogen magnetic powder, which is prepared by the above preparation method.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the HDDR method provided in the present application is used to prepare isotropic samarium-iron-nitrogen magnetic powder, and crushing and aging treatment are performed after the HDDR process. Crushing can ensure the uniform stability of subsequent aging and nitriding. Before nitriding, the samarium-iron alloy is treated by combining high-temperature aging with low-temperature aging, and the aging temperature and time are optimized. The prepared isotropic magnetic powder shows excellent magnetic properties, and has high coercive force while having high magnetic energy product and remanence, and the obtained magnetic powder is loose, which is conducive to the high uniformity of subsequent production of magnetic blocks. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the XRD pattern of the isotropic samarium iron nitrogen magnetic powder of Example 1;

[0030] Figure 2 is the XRD pattern of the isotropic samarium iron nitrogen magnetic powder of comparative example 2;

[0031] Figure 3 is a morphology picture of the isotropic samarium iron nitrogen magnetic powder X500 of Example 1;

[0032] Figure 4 is a morphology picture of the isotropic samarium iron nitrogen magnetic powder X1000 of Example 1;

[0033] Figure 5 is a morphology picture of the isotropic samarium iron nitrogen magnetic powder X500 of comparative example 2;

[0034] Figure 6 This is the morphology of the isotropic samarium iron nitrogen magnetic powder X1000 of comparative example 2. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0037] Example 1

[0038] According to Sm 2 Fe 17 The proportion of Sm and Fe was weighed with an excess of 10%, and the metal was smelted and rapidly solidified to form samarium iron alloy flakes. The melt temperature was 1480°C and the speed of the water-cooled copper roller was 1.5 m / s. The samarium iron alloy flakes were successively hydrogen crushed and jet milled to obtain a particle size of D 50 It is a 9.8 micron powdered samarium-iron alloy; the hydrogen crushing temperature is 160°C, the pressure is 0.05MPa, and the treatment time is 6h.

[0039] The powdered samarium-iron alloy was subjected to HDDR treatment. The specific process of HDDR is: heating from room temperature to 850°C under vacuum conditions for 2 hours; disproportionation at 850°C and 0.05MPa hydrogen atmosphere for 2 hours; slowly heating to 900°C for vacuum dehydrogenation treatment; 0.08MPa argon filling treatment at 900°C for 1 hour; vacuum deargonization at 900°C for 1 hour; and rapid cooling under vacuum after deargonization for 1 hour.

[0040] The isotropic alloy block is crushed again to a particle size D 50 The isotropic alloy powder is heated to 620℃ and kept at this temperature for 15min (T 1), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0041] Finally, the isotropic alloy powder after aging treatment was subjected to high temperature nitriding treatment. The nitriding temperature was 530°C, the nitriding pressure was 0.6MPa, the nitriding gas used was nitrogen, and the nitriding time was 12h to obtain Sm 2 Fe 17 N 3 Isotropic magnetic powder.

[0042] Example 2

[0043] According to Sm 2 Fe 17 The proportion of metal Sm and Fe was weighed with an excess of 10% Sm, and the melt temperature was 1450°C, and the speed of the water-cooled copper roller was 1.2 m / s. The Sm-Fe alloy flakes were successively hydrogen crushed and jet milled to obtain a particle size of D 50 It is a powdered samarium-iron alloy of 9.7 microns; the hydrogen crushing temperature is 120℃, the pressure is 0.06MPa, and the treatment time is 7.5h;

[0044] The powdered samarium-iron alloy was subjected to HDDR treatment. The specific process of HDDR is: heating from room temperature to 850°C under vacuum conditions for 2 hours; disproportionation at 850°C and 0.05MPa hydrogen atmosphere for 2 hours; slowly heating to 900°C for vacuum dehydrogenation treatment; 0.08MPa argon filling treatment at 900°C for 1 hour; vacuum deargonization at 900°C for 1 hour; and rapid cooling under vacuum after deargonization for 1 hour.

[0045] The isotropic alloy block is crushed again to D 50 The isotropic alloy powder is heated to 620℃ and kept at this temperature for 20min (T 1 ), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0046] Finally, the isotropic alloy powder after aging treatment was subjected to high temperature nitriding treatment. The nitriding temperature was 530°C, the nitriding pressure was 1.0 MPa, the nitriding gas used was nitrogen, and the nitriding time was 10 h to obtain Sm 2 Fe 17 N 3 Isotropic magnetic powder.

[0047] Example 3

[0048] The preparation method of Example 1 is different in that the specific process of aging treatment is: firstly heating to 580°C and keeping the temperature for 15 min (T 1), then cooled to 250℃ and kept for 1h (T 2 ).

[0049] Example 4

[0050] According to the preparation method of Example 1, the difference is that the specific process of aging treatment is: first heating to 580°C and keeping warm for 20 minutes (T 1 ), then cooled to 270℃ and kept for 1.5h (T 2 ).

[0051] Comparative Example 1

[0052] The preparation method is the same as in Example 1, except that no aging treatment is performed.

[0053] Comparative Example 2

[0054] The preparation method of Example 1 is different in that the aging treatment method is to heat at 250°C for 1.5h (T 2 ).

[0055] Comparative Example 3

[0056] The preparation method of Example 1 is different in that the aging treatment method is to first heat to 660°C and keep warm for 15 minutes (T 1 ), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0057] Comparative Example 4

[0058] The preparation method of Example 1 is different in that the aging treatment method is to first heat to 500°C and keep the temperature for 15 minutes (T 1 ), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0059] Comparative Example 5

[0060] The preparation method of Example 1 is different in that the aging treatment method is to first heat to 620°C and keep warm for 5 minutes (T 1 ), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0061] Comparative Example 6

[0062] The preparation method of Example 1 is different in that the aging treatment method is to first heat to 620°C and keep warm for 40 minutes (T 1 ), then cooled to 250℃ and kept for 1.5h (T 2 ).

[0063] The magnetic powder obtained in the embodiment and the comparative example was tested, wherein the density was tested by taking 10g of magnetic powder and mixing it with an organic binder, taking 4g and pressing it into a test block with an outer diameter of 10mm under constant pressure, and then measuring the outer dimensions to determine the density. The magnetic properties of the magnetic powder were measured using a vibrating sample magnetometer (VSM). The test results are shown in Table 1 below:

[0064] Table 1: Magnetic powder test results of examples and comparative examples

[0065]

[0066] It can be seen from the above that, combined with the data results of the above embodiments and comparative examples, T 1 Aging time 15min~20min, aging temperature T 1 At 580℃~620℃, the density, energy product and remanence of magnetic powder increase with increasing temperature. 1 Too high, the magnetic properties will decrease significantly, and the aging temperature T 1 Too low, the treatment effect is not obvious. 1 When the aging temperature is between 580℃ and 620℃, T 1 The best aging time is 15min to 20min. 1 If the aging time is too short, the treatment effect is not obvious; if the aging time is too long, the magnetic properties will be reduced.

[0067] Example 1 The XRD pattern of SmFeN magnetic powder is shown in Figure 1 As shown, the XRD spectrum of the samarium iron nitrogen magnetic powder of comparative example 2 is shown in Figure 2 As shown in the figure, it can be seen that the samarium iron nitrogen magnetic powders of Example 1 and Comparative Example 2 both show obvious Sm 2 Fe 17 N 3 The diffraction peaks of Sm and α-Fe 2 Fe 17 N 3 The diffraction peak intensity is significantly higher than that of α-Fe. Figure 1 and Figure 2 It can be seen that the samarium iron nitrogen magnetic powder Sm in Example 1 2 Fe 17 N 3 The diffraction peak intensity is higher, indicating that the main phase content of the magnetic powder in Example 1 is higher and the α-Fe content is reduced.

[0068] Figure 3 and Figure 4 They are the morphology pictures of samarium iron nitrogen magnetic powder of Example 1 at different magnifications; Figure 5 and Figure 6 They are the morphology pictures of samarium iron nitrogen magnetic powder of comparative example 2 at different magnifications; Figure 3 to Figure 6It can be seen that the magnetic powders of Example 1 and Comparative Example 2 do not show obvious agglomeration, and relatively loose magnetic powders can be obtained. It can be seen that the high-temperature aging treatment under appropriate conditions in Example 1 of the present application will not cause agglomeration of the magnetic powders.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and not to limit it. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present application can still be modified or some technical features can be replaced by equivalents, which should all be included in the scope of the technical solution requested for protection in this application.

Claims

1. A method for preparing isotropic samarium iron nitrogen magnetic powder, characterized in that: The following steps are involved: S1, according to Sm2Fe 17 Proportioning, weighing metal Sm and Fe with an excess of 5% to 10% Sm, smelting and rapid solidification to form samarium-iron alloy flakes; S2, crushing the samarium-iron alloy flakes to obtain a powdered samarium-iron alloy having a particle size of 5 μm to 15 μm; S3, performing HDDR treatment on the powdered samarium-iron alloy of the above particle size to obtain an isotropic alloy block; S4, crushing the isotropic alloy block to a particle size of 5 microns to 15 microns, and performing aging treatment to obtain isotropic alloy powder; The aging treatment is to heat the crushed isotropic alloy block to 580℃~620℃ for 15min~20min, and then cool it to 250℃~270℃ for 1h~2h. S5. The isotropic alloy powder after aging treatment is subjected to high temperature nitriding treatment to obtain Sm2Fe 17 N3 isotropic magnetic powder; The melting and rapid solidification in S1 uses a melt temperature of 1450°C to 1500°C and a water-cooled copper roller speed of 1.2m / s to 1.5m / s; The crushing in S2 includes hydrogen crushing and air flow milling in sequence; the hydrogen crushing in S2 is carried out in hydrogen at a temperature of 120°C to 180°C and a pressure of 0.04MPa to 0.06MPa for 0.5h to 10h to cause the samarium-iron alloy flakes to expand and break to obtain a samarium-iron alloy coarse powder; The specific process of HDDR in S3 includes the following steps: (1) Vacuum: Heating from room temperature to 850°C under vacuum conditions for 2 hours; (2) Disproportionation: Disproportionation at 850°C in a hydrogen atmosphere of 0.01MPa to 0.1MPa for 2h; (3) Dehydrogenation: slowly raise the temperature to 900°C for vacuum dehydrogenation treatment; (4) Argon filling: at 900°C, 0.01MPa~0.1MPa argon filling for 1h; (5) Vacuum deargonization: vacuum deargonization at 900 °C for 1 h; (6) Vacuum rapid cooling: After the argon removal is completed, rapid cooling is completed under vacuum, and the cooling time is 1 hour; The nitriding process in S5 is: the nitriding temperature is 530° C., the nitriding pressure is 0.1 MPa to 1.0 MPa, the nitriding gas used is nitrogen, and the nitriding time is 10 h to 20 h.

2. An isotropic samarium iron nitrogen magnetic powder, characterized in that: It is prepared by the preparation method as claimed in claim 1.

Citation Information

Patent Citations

  • Samarium-iron-nitrogen magnetic powder and preparation method thereof

    CN112863798A

  • Preparation method of high-performance composite magnetic powder

    CN116072366A

Cited By

  • A rolled magnetic sheet and its preparation method

    CN120545088B